O problemach badania sztuki w archeologii - Ewa Bugaj (Przegląd Archeologiczny)
In the article, the author attempts to assess the validity of including prehistoric and ancient artefacts in the category of art and considers the problems of studying art in archaeology in the context of the most important transformations of cultural philosophical concepts concerning visual experience. It raises the issues of defining art and aesthetics by discussing essentialist and anti-essentialist approaches, presents a whole range of conceptualisations of art in archaeology and the methods of its analysis, taking into account traditional works, as well as new ones based on social constructivism and postmodernity, focussing especially on the original achievements of Polish researchers in this regard.